2018
DOI: 10.1093/mnras/sty3175
|View full text |Cite
|
Sign up to set email alerts
|

The distance sum rule from strong lensing systems and quasars – test of cosmic curvature and beyond

Abstract: Testing the distance-sum-rule in strong lensing systems provides an interesting method to determine the curvature parameter Ω k using more local objects. In this paper, we apply this method to a quite recent data set of strong lensing systems in combination with intermediate-luminosity quasars calibrated as standard rulers. In the framework of three types of lens models extensively used in strong lensing studies (SIS model, power-law spherical model, and extended power-law lens model), we show that the assumed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 66 publications
6
41
1
Order By: Relevance
“…Therefore, more well-measured strong lensing events might be very useful for reducing the bias in estimation of curvature. In this sense, analyzing simulated SGL observations from Large Synoptic Survey Telescope (LSST) can give some predictions for constraints on cosmological parameters (Collett 2015;Cao et al 2018;Qi et al 2018;Ma et al 2019). Qi et al (2018) have found that, combining about 16000 strong lensing events combined with the distance information provided by 500 compact radio quasars, one can constrain the cosmic curvature with an accuracy of Ω k 10 −3 , which is comparable to the precision of Planck 2015 results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, more well-measured strong lensing events might be very useful for reducing the bias in estimation of curvature. In this sense, analyzing simulated SGL observations from Large Synoptic Survey Telescope (LSST) can give some predictions for constraints on cosmological parameters (Collett 2015;Cao et al 2018;Qi et al 2018;Ma et al 2019). Qi et al (2018) have found that, combining about 16000 strong lensing events combined with the distance information provided by 500 compact radio quasars, one can constrain the cosmic curvature with an accuracy of Ω k 10 −3 , which is comparable to the precision of Planck 2015 results.…”
Section: Resultsmentioning
confidence: 99%
“…Our procedure follows the phenomenological model which quantifies the luminosity L and redshift z dependence of the linear sizes of quasars as (Gurvtis. 1994;Gurvtis et al 1999;Cao et al 2017a;Qi et al 2018)…”
Section: Distances: D L and D Smentioning
confidence: 98%
See 3 more Smart Citations